Best Practice of Village Management Policy During the Covid-19 Pandemic (Case Study of Tourism Sector Economic Recovery of Nglanggeran Village) - Fitri Azmi, Ilima; Listanto, Virgiawan (International Journal of Science, Technology & Management, 2023)
Tourism villages are essential in improving the community's welfare and driving the local and regional economy. Meanwhile, the Covid-19 pandemic has directly impacted the decline in tourist visits, both domestic and foreign, resulting in the loss of potential economic income for the community. This research applies a qualitative descriptive approach and aims to describe how community-based tourism in Nglanggeran Tourism Village is managed and adapted amid the Covid-19 pandemic using the Narrative Policy Framework (NPF). NPF elements (setting, characters, plot and moral) and content play an important role in shaping policy processes and outcomes so they can explain the policy process of Nglanggeran Tourism management policy to recover the economy amid the Covid-19 pandemic. The study shows that the setting problem in this study is the struggle to conceive a management policy for Nglanggeran Tourism Village to survive the covid 19 pandemic. The victims were harmed by the existence of villains (the Covid-19 pandemic) were rural communities whose daily income was mainly from tourism management. The policy recovery management was successful because the heroes have worked a big deal in their role to achieve the success of tourism.